“ISSUES AND CHALLENGES OF WOMEN EMPOWERMENT IN BANGALORE RURAL DISTRICT” (International Journal of Food and Nutritional Sciences, 2022)
Women have been representing half of the entire population and one-third of the work force in all sectors, but they receive only one-tenth of the global income and less than one percent of world property. Still in modern era she has been suffering from violation of her rights. Such an approach provides the women with a constitutional platform to stand up to men, to raise their voice on issues concerning women oppression, exploitation, and related issues and thus in effect, providing them with an identity in an orthodox male dominated socio-political set up, in addition to providing a much needed forum to seek redressal of problems directly affecting them: the true essence of empowerment. The process of empowerment is multi-dimensional and it enables women to realise their full destiny and powers in all spheres of life. A woman’s empowerment begins with consciousness—perceptions about herself and her rights, her capabilities and her potentials, awareness of how gender and socio-cultural and political forces affect her.